Plasma and breast milk pharmacokinetics of suvorexant in healthy lactating women - Jacqueline McCrea; Andrew Litovsky; Prachi Wickremasingha; Nairita Ghosal; Brad Roadcap; Robert Valesky; Robin Lee; Leea D. Reed; Ming Wang; Wei Fang; Rebecca Wrishko (British Journal of Clinical Pharmacology, 2026)
Aim This paper aims to evaluate the plasma and breast milk pharmacokinetics of suvorexant, an orexin receptor antagonist used to treat insomnia at a maximum dose of 20 mg, in healthy lactating women. Methods The paper reports on an open‐label Phase 1 study in 12 healthy lactating women. Participants received a single oral dose of 20‐mg suvorexant following an overnight fast. Blood and breast milk samples for determination of suvorexant and its hydroxy suvorexant metabolite (M9) pharmacokinetics were collected up to 36 h postdose. Participants were required to discontinue feeding their infants with breast milk from study intervention through 60 h postdose to minimize the risk of exposure of suvorexant to an infant. Results Following a 20‐mg dose, suvorexant exposures in breast milk were markedly lower than plasma exposures (in terms of both area‐under‐the‐plasma concentration‐over‐time‐curve [AUC] and C max ) as indicated by the breast milk to plasma ratio of 0.077 to 0.080. The mean amount of suvorexant recovered in breast milk by 36 h was 0.011 mg. Approximately 82% of the suvorexant that was excreted in breast milk was excreted by 24 h. The mean estimated theoretical infant daily dose was 0.0016 mg/kg/day, reflecting a relative infant dose of approximately 0.7% of the body weight normalized maternal dose. Conclusion Following a 20‐mg dose in healthy lactating women, suvorexant exposure in breast milk was markedly lower than plasma exposure. The mean estimated theoretical infant daily dose was less than 1% of the maternal dose.